2022
DOI: 10.3390/en15093021
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic-Thermal (PV-T) Systems for Combined Cooling, Heating and Power in Buildings: A Review

Abstract: Heating and cooling (H/C) represent the largest share of energy consumption worldwide. Buildings are the main consumers of H/C, while the share of renewable energy for H/C provision still represents a low percentage, 22.0% in 2019. Hybrid photovoltaic-thermal (PV-T) systems are gaining increasing attention both in research and in applications, as they generate both electricity and useful heat simultaneously. The relevance and potential of PV-T collectors and their integration into wider systems are evident, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 183 publications
0
11
0
Order By: Relevance
“…Their results confirmed that the thermal efficiency of the collector could be improved by 20% according to air distribution methods [27]. In addition to these studies, other previous research has been conducted to enhance the heat transfer performance of the PVT air collector [28][29][30][31].…”
Section: Introductionmentioning
confidence: 54%
“…Their results confirmed that the thermal efficiency of the collector could be improved by 20% according to air distribution methods [27]. In addition to these studies, other previous research has been conducted to enhance the heat transfer performance of the PVT air collector [28][29][30][31].…”
Section: Introductionmentioning
confidence: 54%
“…These systems can generate electricity and heat together. 6 A PVT system is an integration of a heat exchanger and a PV module together, where the heat accumulated in the PV panel body is absorbed by the associated collector and dissipated in other applications. In this case, the module cools down and its electrical efficiency improves as well as the heat extracted from it is used as thermal energy.…”
Section: Introductionmentioning
confidence: 99%
“…During the past 2 decades, the attention of researchers concerned with the impact of cell temperature on its performance has been focused toward new systems consisting of PV modules connected to heat exchangers, commonly referred to as photovoltaic thermal (PVT) systems. These systems can generate electricity and heat together …”
Section: Introductionmentioning
confidence: 99%
“…A PID controller allows the adjustment of a cooling mechanism such as a fan or heat sink to regulate the temperature of the solar panel. There are other works dedicated to the development of solar cell technologies and the mounting structures of PV modules, such as, e.g., [19][20][21][22], aiming at extracting more energy.…”
Section: Introductionmentioning
confidence: 99%
“…Given the reality of global warming, it is likely that cooling and heating needs in buildings will increase. In this regard, the use of a hybrid PV/T system appears to be a very suitable solution as these systems can supply both heating and cooling depending on the specific needs of the user [22][23][24][25]. While this type of hybrid system has advantages, they can also have disadvantages related to the production and installation costs of PV-T collectors, which are still high.…”
Section: Introductionmentioning
confidence: 99%